Merger of Street Railway Corporations : hearings before the United States House Committee on the District of Columbia, Subcommittee on Public Utilities, Seventy-First Congress, second session, on Jan. 21, Mar. 18, 22, 24, 25, 27, 1930. (U.S. Congressional Hearings., 1930)
Considers (71) H.J. Res. 159.